THE VALUATION OF ACCOUNTS AT CURRENT COST. - Gordon, Myron J. (The Accounting Review, 1953)
When accounts are kept on a historical cost basis, the opening balances of the deferred cost accounts are valued at prices prevailing in prior periods. Insofar as these opening balances remain deferred, the dosing balances of these balance sheet accounts do not reflect current cost. Insofar as these balances are expensed to revenue, the related income statement accounts also do not reflect current cost. The capital gains created by the adjustments to the deferred cost accounts are carried to a statement of capital gains, and the conventional income statement is appropriately renamed the operating income statement. Also, the retained earnings account is replaced with two accounts, one of the retained earnings from operations and the other the aggregate capital gain. The operating income and the capital gains of a period are carried to their respective net worth accounts. The above adjustments result in an operating statement in which revenue and all charges to revenue are measured in current dollars. This statement allows the analysis of performance in that all items are valued in the prices of the same period, and this period is the current period. On the other hand, the valuation income statement dearly presents the gain or loss in the legal unit of account due to the change in prices of assets carried forward from the prior period. The balance sheet offers the same advantages for analysis as the operating income statement in that real assets are valued at their current cost, and monetary assets and liabilities are valued at the actual amounts involved. The balance sheet is not a mix of historical and current cost valued in the purchasing power dollars of a prior period. The current cost accounts provide two significant measures of real profit. Total monetary income, which includes capital gains as well as operating income, is the difference between the opening and the closing net worth.